2014
DOI: 10.1080/02763893.2014.930368
|View full text |Cite
|
Sign up to set email alerts
|

Giving Back and Staying Put: Volunteering as a Stabilizing Force in Relocation

Abstract: Relocation in older adulthood has been shown to have health-related and environmental triggering factors. This study explores the relationship between volunteering in a community and relocation. Using data from 2008 and 2010 Health and Retirement Study, which included 9,220 community-dwelling older individuals who were 65 years and older, our findings show that volunteering significantly reduces the likelihood of relocating out of the area, and such relationship is partially mediated by having friends nearby. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…A total of 74 studies were published in peer-reviewed journals [ 10 , 21 – 28 , 30 99 ]; nine more were retrieved from doctoral theses [ 100 – 108 ] and three others from book chapters reviewed by editorial committees [ 29 , 109 , 110 ]. Over half were published after 2005 (n = 50) [ 10 , 21 – 23 , 25 39 , 44 , 46 – 48 , 51 , 53 , 55 58 , 60 62 , 64 66 , 68 , 69 , 71 , 74 , 77 , 78 , 80 , 81 , 84 – 86 , 88 , 90 92 , 96 , 98 , 99 , 106 ]. Over three quarters of independent studies were conducted in the USA (n = 48) [ 21 , 24 , 31 , 33 , 36 – 38 , 40 43 , 47 ,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 74 studies were published in peer-reviewed journals [ 10 , 21 – 28 , 30 99 ]; nine more were retrieved from doctoral theses [ 100 – 108 ] and three others from book chapters reviewed by editorial committees [ 29 , 109 , 110 ]. Over half were published after 2005 (n = 50) [ 10 , 21 – 23 , 25 39 , 44 , 46 – 48 , 51 , 53 , 55 58 , 60 62 , 64 66 , 68 , 69 , 71 , 74 , 77 , 78 , 80 , 81 , 84 – 86 , 88 , 90 92 , 96 , 98 , 99 , 106 ]. Over three quarters of independent studies were conducted in the USA (n = 48) [ 21 , 24 , 31 , 33 , 36 – 38 , 40 43 , 47 ,…”
Section: Resultsmentioning
confidence: 99%
“…Over half were published after 2005 (n = 50) [ 10 , 21 – 23 , 25 39 , 44 , 46 – 48 , 51 , 53 , 55 58 , 60 62 , 64 66 , 68 , 69 , 71 , 74 , 77 , 78 , 80 , 81 , 84 – 86 , 88 , 90 92 , 96 , 98 , 99 , 106 ]. Over three quarters of independent studies were conducted in the USA (n = 48) [ 21 , 24 , 31 , 33 , 36 – 38 , 40 43 , 47 , 51 , 54 , 55 , 57 , 58 , 62 , 63 , 65 67 , 70 , 71 , 73 , 75 , ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…or death of a spouse. Recent work has indicated that issues of relocation can be understood in terms of an individual’s volunteer experiences in a community (Author, 2014b) and individual and family decisions about the older adult’s disease progression of neurocognitive disorders (Author, 2015). …”
Section: Introductionmentioning
confidence: 99%